In vitro evaluation of novel chitosan derivatives sheet and paste cytocompatibility on human dermal fibroblasts - Abdull Rasad, Mohammad Syaiful Bahari; Halim, Ahmad Sukari; Hashim, Kamaruddin; Abdul Rashid , Ahmad Hazri; Yusof, Norimah; Shamsuddin, Shaharum (Elsevier Ltd., 2010)
The cytocompatibility of novel chitosan derivative sheets and pastes were evaluated in vitro for possible utilization in wound dressing applications for wound healing. In this study, the cytotoxicity of oligochitosan (O-C), N,O-carboxymethyl-chitosan (NO-CMC) and N- carboxymethyl-chitosan (N-CMC) derivatives in sheet like and paste forms were evaluated using primary normal human dermal fibroblast cultures and hypertrophic scars; a fibrotic conditions representing a model of altered wound healing with overproduction of extracellular matrix and fibroblast hyperproliferative activity. Cytotoxicities of these chitosan derivatives were assessed using 3-[4,5-dimethyl-2-thiazolyl]-2,5-diphenyl tetrazolium bromide (MTT) assay. The results indicate that both chitosan derivative sheets and pastes have appropriate cytocompatibility and appear promising as safe biomaterials with potential wound healing applications. The SH120 (NO-CMC) derivatives sheet exhibited highest cytocompatibility property and may be regulated by MMP-13 in controlling the cell growth and its expression level.